Diagnostic accuracy of CBNAAT (Gene-Xpert) Vs liquid culture in clinically diagnosed presumptive childhood tuberculosis admitted in Pt. J.N.M. Medical College & Dr. Bhim Rao Ambedkar Memorial Hospital, Raipur (C.G.) - Dr. Sharja Phuljhele; Dr. Pratima Beck; Dr. Ashish Sinha; Dr. Anil Kumar Saroj (Pediatric Review: International Journal of Pediatric Research, 2019)
Background: Paediatric tuberculosis comprises 10% of all tuberculosis in developing countries. Smear microscopy is diagnostic for Pulmonary TB whereas for extra-pulmonary TB, CBNAAT (Gene-Xpert) and liquid-culture are available choices.Objectives: To establish the comparative diagnostic efficacy of CBNAAT and Liquid-culture in clinically presumptive childhood Tuberculosis.Outcome: Assess sensitivity and specificity of CBNAAT Vs Liquid-culture in clinically diagnosed presumptive childhood tuberculosis.Material & Method: After approval from institutional ethical committee this Cross-sectional study was performed in department of paediatrics Pt. J. N. M. Medical College, Raipur C.G. Total 97 paediatric presumptive TB cases were enrolled for systematic screening from June-2017 to July-2018. Samples were collected and analysed by CBNAAT and liquid-culture. Data for Diagnostic efficacy of both techniques were analysed with appropriate statistical method.Results: Among study subject group 41.2% belongs to 11-15 age-group and 53.6% were female. Majority of them belongs to joint family (81.4%) and low-socioeconomic (85.6%) status. Among 97 presumptive cases CBNAAT was positive in 24.7% whereas liquid-culture was positive in 22.7%. CBNNAT has sensitivity (100%) and specificity (98.61%) when compared with liquid-culture as gold-standard. It has 95.65% positive and 100% negative predictive values. CBNAAT had 100% of sensitivity and specificity in diagnosis of abdominal-tuberculosis and TB-meningitis. In Pulmonary-TB diagnosis its specificity reduced to 98%.Conclusion: CBNAAT is equally efficacious diagnostic tool to diagnose clinically presumptive TB cases and it should be used in public health system for early diagnosis of paediatric tuberculosis.